Criminalistic and Legal Aspects of Documenting the Crime of Deportation of Ukrainian Children as a Form of Genocide in the Context of Armed Aggression by the Russian Federation (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article provides a comprehensive study of the criminalistic, legal, and international legal aspects of documenting the crime of forced deportation of Ukrainian children committed during the armed aggression of the Russian Federation against Ukraine. It is noted that the forcible transfer of children from the temporarily occupied territories of Ukraine to the Russian Federation and their subsequent detention in specialised institutions or foster families is systematic, organised and planned in nature, which corresponds to the characteristics of the crime of genocide as defined by the 1948 UN Convention on the Prevention and Punishment of the Crime of Genocide.The current regulatory framework governing the prevention of crimes related to the illegal removal and detention of children is analysed, and problematic aspects of the legal classification of such acts under the Criminal Code of Ukraine are outlined. The provisions of international humanitarian law, in particular the Rome Statute of the International Criminal Court, are considered in the context of international recognition of forced deportation as a war crime and a crime against humanity.Particular attention is paid to the criminalistic aspects of documenting this crime. Methods of collecting, recording and verifying evidence are considered, including the use of digital technologies, geolocation data, photo and video materials that allow the identification of the routes of movement and whereabouts of children. The peculiarities of interrogating victims, witnesses and persons involved in organising the deportation are analysed, taking into account the age and psychological characteristics of children as a vulnerable category of persons.The role and importance of international cooperation in documenting the facts of forced deportation is considered, in particular the activities of the Joint Investigation Team, the Office of the Prosecutor of the International Criminal Court, as well as special mechanisms of the UN and the Organisation for Security and Cooperation in Europe. It is emphasised that cooperation between national and international institutions ensures an adequate level of evidence collection and increases the effectiveness of the process of bringing those responsible to justice at the national and international levels.It was concluded that the documentation of the crime of forced deportation of Ukrainian children should be based on a comprehensive combination of forensic and legal approaches that take into account international standards of evidence, children's rights and humanitarian principles. The need to improve national legislation regarding the classification of genocide as a crime is justified, as is the development of a unified methodology for the forensic documentation of such crimes in order to ensure the inevitability of punishment for the perpetrators and the restoration of justice for the child victims.